Evaluation of the innate immune responses to influenza and live-attenuated influenza vaccine infection in primary differentiated human nasal epithelial cells. Issue 45 (27th October 2017) - Forero, Adriana; Fenstermacher, Katherine; Wohlgemuth, Nicholas; Nishida, Andrew; Carter, Victoria; Smith, Elise A.; Peng, Xinxia; Hayes, Melissa; Francis, Doreen; Treanor, John; Morrison, Juliet; Klein, Sabra L.; et al.
Graphical abstract: Abstract: The host innate immune response to influenza virus is a key determinant of pathogenic outcomes and long-term protective immune responses against subsequent exposures. Here, we present a direct contrast of the host responses in primary differentiated human nasal epithelial cell (hNEC) cultures following infection with either a seasonal H3N2 influenza virus (WT) or the antigenically-matched live-attenuated vaccine (LAIV) strain. Comparison of the transcriptional profiles obtained 24 and 36 h post-infection showed that the magnitude of gene expression was greater in LAIV infected relative to that observed in WT infected hNEC cultures. Functional enrichment analysis revealed that the antiviral and inflammatory responses were largely driven by type III IFN induction in both WT and LAIV infected cells. However, the enrichment of biological pathways involved in the recruitment of mononuclear leukocytes, antigen-presenting cells, and T lymphocytes was uniquely observed in LAIV infected cells. These observations were reflective of the host innate immune responses observed in individuals acutely infected with influenza viruses. These findings indicate that cell-intrinsic type III IFN-mediated innate immune responses in the nasal epithelium are not only crucial for viral clearance and attenuation, but may also play an important role in the induction of protective immune responses with live-attenuated vaccines.